2019
DOI: 10.18502/ijm.v11i3.1315
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent detection of cagA, vacA, sodB and hsp60 virulence genes and their relationship with clinical outcomes of disease in Helicobacter pylori isolated strains of southwest of Iran

Abstract: Background and Objectives: Helicobacter pylori is a Gram-negative spiral-shaped bacterium that contaminates more than half of the world's inhabitants, and infection with this bacterium is associated with some gastric disorders. Also, 5% to 10% of H. pylori genes are specific to this bacterium and many bacterial virulence factors fall into this group. The cagA, vacA, sodB and hsp60 are among important virulence factors of H. pylori. Materials and Methods: A gastric biopsy specimen was taken from 341 gastr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…In our study, the prevalence of cagA in H. pylori strains was 90.6% that was nearly similar to previous reports from Vietnam at 95% ( Uchida et al 2009 ), North America at 88% ( Yamaoka et al 1999 ), and Sweden at 82% ( Ryberg et al 2008 ). In our study, the vacA gene was detected in most of the isolated H. pylori strains (95.3%) consistent with other reports ( Ezzat et al 2012 ; Amin et al 2019 ). Also, we have reported the prevalence of the vacAm1 allele at 52.8%, which was higher than that of vacAm2 (42.5%).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In our study, the prevalence of cagA in H. pylori strains was 90.6% that was nearly similar to previous reports from Vietnam at 95% ( Uchida et al 2009 ), North America at 88% ( Yamaoka et al 1999 ), and Sweden at 82% ( Ryberg et al 2008 ). In our study, the vacA gene was detected in most of the isolated H. pylori strains (95.3%) consistent with other reports ( Ezzat et al 2012 ; Amin et al 2019 ). Also, we have reported the prevalence of the vacAm1 allele at 52.8%, which was higher than that of vacAm2 (42.5%).…”
Section: Discussionsupporting
confidence: 92%
“…Molecular detection of cagA , sodB , hsp60 , and vacA virulence genes of H. pylori using multiplex PCR. Multiplex PCR was undertaken following the coming steps simultaneously: beginning with incubation for 5 minutes at 95°C; then 34 cycles consisted of one minute at 94°C, then another one minute for primer annealing at 55°C, followed by extension for 60 seconds at 72°C; to be finished with the final extension step at 72°C for ten minutes ( Amin et al 2019 ). The reaction volume was 25 μl and consisted of a PCR master mix (Fermentas, Germany) that included 4 mM MgCl 2 , 0.4 mM of each dNTP, and 0.05 U/μl Taq DNA polymerase.…”
Section: Methodsmentioning
confidence: 99%
“…In another study, 83% of H. pylori strains harbored either vacA s1m1 or vacA s2m2 (223/269) [17] . In a study conducted by Amin and colleagues (2019), 100% of the samples were vacA positive [27] . According to a histopathology report from Colombia in 2019, 44.2% of gastric biopsy samples were positive for the presence of vacA gene [27] .…”
Section: Discussionmentioning
confidence: 98%
“…In a study conducted by Amin and colleagues (2019), 100% of the samples were vacA positive [27] . According to a histopathology report from Colombia in 2019, 44.2% of gastric biopsy samples were positive for the presence of vacA gene [27] . In another study, the prevalence rate of cagA and vacA was reported to be 82.6 and 73.91% among patients with gastric cancer, respectively [28] .…”
Section: Discussionmentioning
confidence: 98%
“…CagA is also a highly antigenic protein that is associated with prominent inflammatory reactions produced by the secretion of interleukin-8 (IL-8). A study examining immune reagents for the diagnosis of CagA H. pylori , produced and identified the first set of monoclonal antibodies against CagA [ 17 ]. In addition, chronic infection with H. pylori was found to be a major risk factor for developing GC.…”
Section: Mechanisms Of Pathogenic Factors In H Pylorimentioning
confidence: 99%